Actualizing Human Rights Global Inequality, Future People, and Motivation - Philips, Jos (Taylor & Francis, 2020)
"This book argues that ultimately human rights can be actualized, in two senses. By answering important challenges to them, the real-world relevance of human rights can be brought out; and people worldwide can be motivated as needed for realizing human rights. Taking a perspective from moral and political philosophy, the book focuses on two challenges to human rights that have until now received little attention, but that need to be addressed if human rights are to remain plausible as a global ideal. Firstly, the challenge of global inequality: how, if at all, can one be sincerely committed to human rights in a structurally greatly unequal world that produces widespread inequalities of human rights protection? Secondly, the challenge of future people: how to adequately include future people in human rights, and how to set adequate priorities between the present and the future, especially in times of climate change? The book also asks whether people worldwide can be motivated to do what it takes to realize human rights. Furthermore, it considers the common and prominent challenges of relativism and of the political abuse of human rights. This book will be of key interest to scholars and students of human rights, political philosophy, and more broadly political theory, philosophy and the wider social sciences."